1986
DOI: 10.1111/j.1526-4610.1986.hed2609457.x
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Burden of Headache: An Epidemiological Study in the Republic of San Marino

Abstract: SYNOPSIS We examined the socio‐economic consequences of headache in a random sample of 514 working people living inthe Republic of San Marino. Our results show that, in the preceding year, 255 out of 514 (49.6%) suffered fromheadache; 31.9% (164/514) reported decreased efficiency as a consequence of headache; 9.3% (48/514) reportedthat head pain is always severe; 7.4% (38/514) were absent from work because of headache for a total of 338working days lost; 8.4% of all working days lost to illness were due to hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 2 publications
2
5
0
Order By: Relevance
“…This consultation rate is in agreement with previous European reports,-5 but may be somewhat different from that in other areas due to varying cultural and social backgrounds and even to variations in the availability of general practitioners. The higher rates in women are in agreement with most previous studies,5 8 though equal consultation rates in men and women were reported in one study.9 The percentage of subjects who had consulted a specialist or a hospital is in accordance with previous reports.3 10 The frequency of contacts with a chiropractor or physiotherapist was somewhat higher than that reported in a study in the United States,7 but again regional variations in the health service systems and in the level of medical care, as well as different traditions, may influence the findings. The higher consultation rates in subjects with coexisting migraine and tension type headaches compared to subjects with pure migraine and pure tension type headache are in concordance with Berkson's view that subjects with more than one disease are more likely to seek medical care than subjects with only one disease.…”
Section: Medical Servicessupporting
confidence: 91%
“…This consultation rate is in agreement with previous European reports,-5 but may be somewhat different from that in other areas due to varying cultural and social backgrounds and even to variations in the availability of general practitioners. The higher rates in women are in agreement with most previous studies,5 8 though equal consultation rates in men and women were reported in one study.9 The percentage of subjects who had consulted a specialist or a hospital is in accordance with previous reports.3 10 The frequency of contacts with a chiropractor or physiotherapist was somewhat higher than that reported in a study in the United States,7 but again regional variations in the health service systems and in the level of medical care, as well as different traditions, may influence the findings. The higher consultation rates in subjects with coexisting migraine and tension type headaches compared to subjects with pure migraine and pure tension type headache are in concordance with Berkson's view that subjects with more than one disease are more likely to seek medical care than subjects with only one disease.…”
Section: Medical Servicessupporting
confidence: 91%
“…Absence rate and number of days off work due to tension-type headache are similar to those reported in Finland (177). Most other studies dealing with sickness absence have not analysed migraine and tension-type headache separately (31,41,175,179). As for the use of medical services, regional variations and methodological differences have to be considered when comparing the results of work consequences in various studies.…”
Section: Work Consequencessupporting
confidence: 67%
“…In two relatively old studies, one from Finland in 1979 [14] and one from San Marino in 1986 [15], 7% of working individuals had been absent from work in the previous year due headache. In a Danish study of 1992 [16], it was found that 43% of migraineurs (5% of the population) and 12% of TTH patients (9% of the population) had been absent from work during the previous year due to headache, i.e.…”
Section: Economic Impact Of Headachementioning
confidence: 99%